2010
DOI: 10.1016/j.jpsychores.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of stress responsive systems as a risk factor for functional somatic syndromes

Abstract: The etiology of functional somatic syndromes or disorders (FSDs) is generally considered to be a multifactorial interplay between psychological, biological, and social factors. One of the most investigated biological factors is stress responsive system dysfunction. Despite more than twenty years of research of the autonomic nervous system and the hypothalamic-pituitary-adrenal axis, however, it is yet unknown whether dysfunctions in these systems play a causal role in the etiology of FSDs and whether they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 65 publications
(73 reference statements)
2
64
0
2
Order By: Relevance
“…The popularity of the amplification model relies in part on the observation that physical symptom reports are commonly comorbid with symptoms of anxiety and depression (Wessely et al, 1999;Kroenke, 2003) and consistently associated (r = 0.40-0.50) with higher trait negative affectivity (NA; i.e., a pervasive tendency to experience negative affect; Watson and Pennebaker, 1989) and elevated stress levels (Tak and Rosmalen, 2010). Increased symptom reports in primary care have often been interpreted as resulting from elevated autonomic arousal (Kolk et al, 2003;Kirmayer et al, 2004).…”
Section: Peripheral Arousal and Stress-related Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of the amplification model relies in part on the observation that physical symptom reports are commonly comorbid with symptoms of anxiety and depression (Wessely et al, 1999;Kroenke, 2003) and consistently associated (r = 0.40-0.50) with higher trait negative affectivity (NA; i.e., a pervasive tendency to experience negative affect; Watson and Pennebaker, 1989) and elevated stress levels (Tak and Rosmalen, 2010). Increased symptom reports in primary care have often been interpreted as resulting from elevated autonomic arousal (Kolk et al, 2003;Kirmayer et al, 2004).…”
Section: Peripheral Arousal and Stress-related Physiologymentioning
confidence: 99%
“…This picture applies to autonomic function as indicated by heart rate variability: a metaanalysis by Tak et al (2009) found no significant difference between patients with functional somatic disorders and healthy controls after controlling for publication bias. Another review found no differences between patients with functional somatic syndromes and healthy controls in half of the studies, and some evidence of reduced cardiac vagal activity in another half, depending also on the type of functional syndrome (Tak and Rosmalen, 2010). A systematic review of Van Cauwenbergh et al (2014) suggested a reduced cardiac response to a head-up tilt test in chronic fatigue patients in 7 of 8 studies.…”
Section: Authorsmentioning
confidence: 99%
“…Within this account, cognitive behavioural models have become increasingly popular [2][3][4][5]. These models propose a set of predisposing factors (e.g., genetics, personality characteristics, and life events), precipitating factors (e.g., physiological factors and general distress) and perpetuating factors (e.g., physiological, cognitive, behavioural, and social reactions) that each may contribute to the development and maintenance of CFS [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether the altered stress response is a causal factor or a result of the condition is unclear (Tak & Rosmalen, 2010). By contrast, hypocortisolism has also been identified in groups that are exposed to chronic stress, including children raised in Romanian orphanages (Gunnar & Vazquez, 2001) and other chronically stressful environments, such as being an ethnic minority (DeSantis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%